Parallel Metabolomics and Lipidomics of a PSMA/GCPII Deficient Mouse Model Reveal Alteration of NAAG Levels and Brain Lipid Composition - Sedlák, František; Kvasnička, Aleš; Marešová, Barbora; Brumarová, Radana; Dobešová, Dana; Dostálová, Kateřina; Šrámková, Karolína; Pehr, Martin; Šácha, Pavel; Friedecký, David; Konvalinka, Jan (ACS chemical neuroscience, 2024)
Glutamate carboxypeptidase II (GCPII, also known as PSMA or FOLH1) is responsible for the cleavage of N-acetyl-aspartyl-glutamate (NAAG) to N-acetyl-aspartate and glutamate in the central nervous system and facilitates the intestinal absorption of folate by processing dietary folyl-poly-γ-glutamate in the small intestine. The physiological function of GCPII in other organs like kidneys is still not known. GCPII inhibitors are neuroprotective in various conditions (e.g., ischemic brain injury) in vivo; however, their utilization as potential drug candidates has not been investigated in regard to not yet known GCPII activities. To explore the GCPII role and possible side effects of GCPII inhibitors, we performed parallel metabolomic and lipidomic analysis of the cerebrospinal fluid (CSF), urine, plasma, and brain tissue of mice with varying degrees of GCPII deficiency (fully deficient in Folh1, -/-; one allele deficient in Folh1, +/-; and wild type, +/+). Multivariate analysis of metabolites showed no significant differences between wild-type and GCPII-deficient mice (except for NAAG), although changes were observed between the sex and age. NAAG levels were statistically significantly increased in the CSF, urine, and plasma of GCPII-deficient mice. However, no difference in NAAG concentrations was found in the whole brain lysate likely because GCPII, as an extracellular enzyme, can affect only extracellular and not intracellular NAAG concentrations. Regarding the lipidome, the most pronounced genotype-linked changes were found in the brain tissue. In brains of GCPII-deficient mice, we observed statistically significant enrichment in phosphatidylcholine-based lipids and reduction of sphingolipids and phosphatidylethanolamine plasmalogens. We hypothesize that the alteration of the NAA-NAAG axis by absent GCPII activity affected myelin composition. In summary, the absence of GCPII and thus similarly its inhibition do not have detrimental effects on metabolism, with just minor changes in the brain lipidome.
Keywords: FOLH1; Lipidomics; Metabolomics; Dipeptides; Brain; glutamátkarboxypeptidasa II; metabolomika; lipidomika; metabolomics; Glutamate Carboxypeptidase II; folyl-poly-γ-glutamyl hydrolase I; glutamate carboxypeptidase II; Glutamic Acid; lipidy; Animals; N-acetyl-aspartyl-glutamate; lipidomics; zvířata; mozek; myši; dipeptidy; Lipids; Mice; kyselina glutamová